If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-2x + 4) = -4 Reorder the terms: 7(4 + -2x) = -4 (4 * 7 + -2x * 7) = -4 (28 + -14x) = -4 Solving 28 + -14x = -4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + -14x = -4 + -28 Combine like terms: 28 + -28 = 0 0 + -14x = -4 + -28 -14x = -4 + -28 Combine like terms: -4 + -28 = -32 -14x = -32 Divide each side by '-14'. x = 2.285714286 Simplifying x = 2.285714286
| +1-+13= | | 0.12+0.03(y-5)=-0.01(y-4)+0.02 | | 7m-16=47 | | 8x+14=-12x-6 | | 3xy+x^2-2y^2=2 | | 9(3y+6)+3(y+6)= | | -2(5m-2)=2(2+9m)+m | | 4r+11(1-7r)=7+4(1-11r) | | 7p+9q=29 | | 8x-79=3x-9 | | Y=8x-79 | | -0.9156*d^3-0.1962*d^2+422.4163=0 | | 14-4x=-10 | | 6-5x=-59 | | 10x-8=7x+9 | | 13+7x=48 | | 7x+5=95 | | 8x-1=95 | | 13+8x=37 | | 3=6x-15 | | 6-5x=-54 | | 3y+8=8y-17 | | 6x(11+4)=-3 | | 3(10x-2)=8 | | 8x-5=123 | | 15-4x=-9 | | y^2-5y-20=0 | | 16-4x=-4 | | 6-5x=-49 | | 5x+14=-14-2x | | 5x+2y+9z-3x+5z-3y= | | 2+8x=122 |